Perancangan Form Penilaian dan Penerimaan Karyawan untuk Meningkatkan Kualitas Sumber Daya Manusia di One Boulevard Food Court - Liora Madya Elviranita Telaumbanua; Agustinus Setyawan (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
In the era of increasingly fierce business competition, the quality of human resources (HR) is one of the key factors that determine the success of a company. One Boulevard Food Court realizes the importance of HR as a valuable asset that plays a role in ideation, driving performance, and implementing activities to achieve company goals. However, currently, the employee assessment and recruitment process implemented is not optimal in supporting overall HR development. The unstructured system creates problems in determining the quality of prospective employees and evaluating the performance of existing employees. The unclear criteria and subjective assessment process resulted in many employees who did not meet the company's expectations. It is necessary to design a more structured employee assessment and recruitment form to overcome this problem. This formula is designed based on the company's needs analysis and includes criteria to assess employee competencies, skills, and potential. Through this system, One Boulevard Food Court is expected to increase transparency and efficiency in the administration process, as well as ensure that recruited employees meet the required quality.